(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
This article analyzes the process of developing mental (mental) competence of children in preschool educational institutions and its effective methods. The study highlights the stages of formation of children’s thinking, pedagogical technologies that stimulate cognitive activity, ways to develop intellectual abilities through play and interactive methods. Methodological approaches supporting the processes of thinking, perception, memory and attention in preschool children and the role of educators in this process are also analyzed. The article reveals the importance of modern psychological and pedagogical approaches to the formation of the mental potential of children.